PERAN STABILITAS MONETER DAN KETAHANAN GLOBAL DALAM PEMBANGUNAN EKONOMI IKN: TANTANGAN DAN PELUANG - Adzam, Muh; Ayuningsih, Lilis; Biome'eto, Tria Rosaline; Anggraini, Qiqi Reski; Mawarda, Alfia Rahmayanti (Politeknik Bisnis Indonesia, 2024)
The development of the National Capital City (IKN) in East Kalimantan is one of the national strategic projects that aims to encourage equitable economic development and create a new sustainable growth center. However, the success of IKN development is inseparable from major challenges, both at the domestic and global levels, such as macroeconomic stability, climate change, exchange rate fluctuations, and geopolitical dynamics. In this context, monetary stability and global resilience are key elements to ensure that the development of the IKN can run effectively and sustainably. Monetary stability plays an important role in creating a conducive investment climate through inflation control, exchange rates, and interest rate policies that support economic growth. Meanwhile, global resilience strengthens the IKN's ability to adapt to external risks, such as financial crises, climate change, and geopolitical tensions, while taking advantage of opportunities from global economic developments, such as the green energy transition and technological innovation. This article analyzes the relationship between monetary stability and global resilience in facing challenges and taking advantage of IKN development opportunities. Using a descriptive-qualitative approach, this article highlights the importance of synergy between the two elements in creating a resilient and inclusive economic foundation. The results of the analysis show that monetary stability provides a basis for investment and economic growth, while global resilience ensures the sustainability of development in the face of global dynamics. Therefore, the integration of monetary stability and global resilience strategies is an important step to realize the vision of IKN development as a future city that is globally competitive and sustainable.